THE IMPLICATIONS OF STOCK PRICE, LIQUIDITY, AND PROFITABILITY ON THE CONSUMER NON-CYCLICALS SECTOR'S COMPANY VALUE - Diva Kanisa, Ireniza; Imronudin, Imronudin (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. Providing actual data is the aim of the study, such as profitability, liquidity, and stock price analysis, to support the company's valuation. This research was done in 2022 on businesses in the consumer non-cyclical industry. A total of 106 businesses were chosen as sample companies using the purposive selection technique. year of observation based on 2022 cross-sectional data. The data was obtained from the corporation under observation's financial statements as well as several of its auxiliary websites. The study data analysis methodology makes use of the Ordinary Least Squares (OLS) approach and multiple regression analysis with the Eviews12 analysis tool. The study's findings indicate PBV is positively impacted by the stock price probability of 0,0020 < 5% and positively and significantly by the ROE factor of 0,0021 ≤ 5%. Nevertheless, PBV is negatively impacted by CR 0,135 ≥ 5%. Keywords: Stock price; Liquidity; Profitability; Company value